Analysis of impact characteristics of hydraulic column based on bidirectional fluid-structure coupling - LIU Ya; CHEN Yumeng; ZHANG Kun; HUANG Liangsong; QI Yuhao; LI Yuxia; ZHONG Donghu; WEI Xuntao; ZHANG Fujia (Meikuang Anquan, 2022)
As the most important bearing component of the hydraulic support, the bearing performance of the column has a huge influence on the supporting effect of the whole hydraulic support. Especially, when the coal bump disaster occurs, it may cause accidents such as bending, fracture and cylinder explosion of the hydraulic support column. The fluid-structure interaction model of ZF10000/25/38 hydraulic support column is established by Solid Works and Design Modeler software. The hydraulic support column is regarded as a spring, and the equivalent stiffness mathematical model of single telescopic column is derived. Then, the bidirectional transient fluid-structure interaction model of column is simulated by ANSYS Workbench simulation software, and the impact characteristics of coal bump are simulated by introducing triangular wave impact load to study the anti-impact characteristics of the single telescopic column of the hydraulic support. The simulation results show that the maximum stress of hydraulic support column piston rod under impact load is 508 MPa, which occurs at the top, and the maximum stress of cylinder block is 254 MPa, which occurs at the bottom.